Utilization of galiang (crytusperma merkusii) flour in the production of chocolate crinkles - Vivar, Rhodora Carunungan (University of the Philippines Diliman, 1999)
In this study, galiang flour was used to partially substitute all-purpose flour in the production of chocolate crinkles. Several batches of chocolate crinkles having different levels of galiang flour were prepared in the Preliminary Study. The maximum acceptable substitution range was determined to be 45-49%. Phase I involved the production of chocolate crinkles in four batches 46%, 47%, 48%, and 49% galiang flour (based on the total weight of flour). The four were compared on their sensory attributes of the chocolate crinkles. In Phase II, the sample having the chosen substitution level (48%) was produced thrice to assess its replicability. Results showed that no significant differences existed between the three samples due to production runs. In Phase III, the chocolate crinkles produced from the control and experimental formulations were subjected to chemical, microbiological and cost analyses. Results showed that the sample with galiang flour had higher levels of moisture, fat, TAC, fiber, and ash content but a lower protein content. Results of the microbiological examination including total plate, yeast and mold, and coliform counts proved the products to be safe for consumption. The cost of chocolate crinkles with galiang flour was determined to be P3.10 each- 2.65% more than that of the control, which is P3.02.